The Cinema of Mia Hansen-Løve Candour and Vulnerability - Ince, Kate (Edinburgh University Press, 2021)
Since 2007 Mia Hansen-Løve has directed a series of meditative film dramas about families, love, vulnerability and growing up, all of them exceptionally attentive to film's ability to convey the passing of time, separation and loss. As the first book-length study of the films of Mia Hansen-Løve, this volume introduces her cinema to both an academic and a general readership. Exploring her move from acting, via criticism, to directing, the book first investigates the complexity of her situation as a female auteur based in France. With detailed readings of her films up to Maya (2018), it then examines the precariousness of their families, their emphasis on vulnerability, failure, adversity and resilience, the particular candour of Hansen-Løve's filming style, and the vital parts played by music and time in her cinema. It concludes that her cinema may best be regarded as a thoroughly contemporary one, distinguished by a tendency to transcendence that is both ethical and aesthetic.